Plasma spray of nicraly coating on laser surface modified H13 tool steel - Mohamed Reza Zalani, Mohamed Suffian (2022)
This thesis presents experimental study of nickel-based alloy, NiCrAlY coating on laser modified AISI H13 steel using atmospheric plasma spray (APS). AISI H13 steel is often being used as die material in metal forming technology, specifically semi solid metal processing. Repetitive process of incoming high temperature, solidification and rapidly quenched semi solid metal through die, causes erosion and corrosion wear on the die cavity surface. Erosion which was causes by friction and corrosion by chemical reaction mitigate die performance and durability properties. Hence, retaining die properties were crucial to gain optimum semi solid metal processes. This study aims to modify AISI H13 steel substrate surface for enhanced mechanical properties and interfacial bonding with NiCrAlY coating. Mechanical properties of AISI H13 steel surface micro hardness was enhanced from rapid quenching process by pulse laser surface modification. While, interfacial bonding of NiCrAlY coating was enhanced by increasing the percentage of chemical elemental diffusion and the surface roughness asperities for mechanical interlocking. A modified layer of AISI H13 steel with enhanced surface properties was developed using two different laser spot size of 90 µm and 600 µm separately. The mechanical properties and interfacial bonding of NiCrAlY coating on laser surface modified AISI H13 steel substrate were enhanced at different laser parameters. Laser parameters of 90 um spot size used were laser peak power; 0.76 kW and 1.3 kW, pulse rate frequency (PRF); 2500 Hz and 2800 Hz and laser scanning speed; 2.0 mm/s and 6.0 mm/s. While, laser parameters of 600 um spot size used were laser peak power; 1.6 kW and 2.0 kW, pulse rate frequency (PRF); 40 Hz and 60 Hz and laser scanning speed; 14.13 mm/s and 20 mm/s. Prior to NiCrAlY coating, lasered samples being modified by 600 um laser spot size went on sandblasting process. Surface profile such as asperities, valleys depth and peak height and average roughness, Ra also had been analyzed. Asperities at the entire surface profile with low peaks and valleys size promotes wettability of coating particle splats during coating. Elemental analysis showed chemical bonding occurred in coating because of element diffusion. Metastable phase occurred on the laser modified surface inspired atomic diffusion that enhanced coating adhesion. Metastable phase consists of excited energy that promotes atomic diffusion between the laser modified/coating interlayer. Results for coating interfacial toughness obtained by Vickers interfacial indentation test (IIT) were obtained above reference sample toughness measurement which was 2.08 MPa. Interfacial toughness range between 2.02 to 6.54 MPa. For conclusion, interface bonding of NiCrAlY coating is enhanced based from the research objectives. Mechanical interlocking plays an important role for interface bonding of NiCrAlY coating. Surface that contains asperities at whole surface profile, decreasing depth and peaks measurement increased coating adhesion. For atomic bonding, metastable α-Fe phase occurs from laser surface modification assists atomic diffusion in the NiCrAlY coating interlayer. Mechanical interlocking plays major role in the succesful of the NiCrAlY coating adhesion. Hence, NiCrAlY coating on laser modified H13 steel by 600 um laser spot size requires surface post processing using sandblasting. This research findings were important to obtained achievement of coating layer with resistance to erosion and corrosion in the direction of manufacturing sustainability.